Sintesis Asam Etoksi Lignosulfonat sebagai Surfaktan dari Limbah Tandan Kosong Kelapa Sawit - A Ardinal; M Rif'at (Jurnal Litbang Industri, 2017)
Synthesis of ethoxy lignosulfonic acid as a surfactant from a waste of palm oil empty fruit bunch was aimed to isolate lignin, studying the ethylation of the lignin and sulfonation of the alkyl lignin to produce ethoxy lignosulfonic acid moreover to investigate its activity as the surfactant. At first, lignin was isolated from the waste of palm oil empty fruit bunch by sulfate method, then lignin was alkylated with diethylsulfate (DES), and the resulted ethoxy lignin was sulfonated using sodium bisulfite. Each product was characterized by FT-IR and the success of the sulfonation was proven by SEM-EDX. Surfactant test properties included: determination of critical micelle concentration (CMC) with turbidimetry method, foam stability, emulsions index and emulsion stability. Lignin isolation gave lignin as light brown solid in 27.8% yield. Alkylation reaction of lignin with diethyl sulfate produced ethoxy lignin in 83.0% yield. Sulfonation of ethoxy lignin using sodium bisulfite afforded ethoxy lignosulfonic acid in 88.5% yield. It was known that there was a significant increase in oxygen percentage at the sulfonation process. Ethoxy lignosulfonic acid as the surfactant has CMC of 1.6 g/L, the surfactant concentration of 1.5 g/L gave stable foam for 100 minutes, the surfactant has an emulsion index of 35% in a gasoline-water system and 56% in the cooking oil-water system. The emulsion on both systems was stable for four days of measurement.ABSTRAKSintesis asam etoksi lignosulfonat sebagai surfaktan dari limbah tandan kosong kelapa sawit (TKKS) dilakukan dengan tujuan mengisolasi lignin dari TKKS, mempelajari etilasi terhadap lignin dan sulfonasi terhadap etoksi lignin untuk menghasilkan asam etoksi lignosulfonat serta uji aktifitasnya sebagai surfaktan. Lignin diisolasi dari TKKS dengan metode sulfat, lalu dialkilasi dengan dietil sulfat (DES) dan disulfonasi dengan natrium bisulfit. Tiap produk dikarakterisasi dengan FT-IR dan untuk mengetahui keberhasilan sulfonasi diketahui dengan SEM-EDX. Uji sifat surfaktan yang dilakukan antara lain: penentuan konsentrasi kritis misel (KKM) dengan metode turbidimetri, pengukuran kestabilan busa, indeks emulsi dan kestabilan emulsi. Isolasi lignin dari TKKS menghasilkan padatan cokelat terang lignin dengan rendemen 27,8%. Alkilasi lignin dengan DES menghasilkan etoksi lignin dengan rendemen 83,0%. Sulfonasi etoksi lignin dengan natrium bisulfit menghasilkan asam etoksi lignosulfonat dengan rendemen 88,5%. Keberhasilan reaksi sulfonasi etoksi lignin dikonfirmasi dari kenaikan persen atom oksigen menggunakan SEM-EDX. Senyawa asam etoksi lignosulfonat sebagai surfaktan memiliki KKM 1,6 g/L, pada konsentrasi surfaktan 1,5 g/L dan volume busa stabil selama 100 menit. Surfaktan asam etoksi lignosulfonat memiliki indeks emulsi 35% pada sistem bensin-air dan 56% pada sistem minyak goreng-air. Emulsi yang terbentuk pada kedua sistem stabil selama empat hari pengukuran.